Antioxidant response by alfalfa (Medicago sativa L.) to Pb pollution - A study to value the feasibility of soil phytoremediation - Changfeng Liu; Ye Wang; Xiaoyu Zhang; Gong-Ling Zhang; Xuegui Liu; Pinyi Gao; Shuhua Yao (Soil and Water Research, 2022)
With the surrounding environment of Inner Mongolia lead (Pb) ore as the research background, the germination and physio-biochemical effects of Pb stress on alfalfa were discussed to employ this species for the remediation of Pb contaminated soil. Research has shown that a low Pb stress concentration could improve the biological resistance of alfalfa seeds, while a high Pb stress concentration cannot be tolerated. Interestingly, when the Pb concentration was 5 mg/L, the germination rate of the seed was promoted, and the chlorophyll content was especially increased. As the Pb content and stress increased, the amount of malondialdehyde (MDA), H2O2, catalase (CAT) increased; while the root cell viability, chlorophyll and soluble protein content decreased. In consequence, alfalfa was tolerant to Pb stress of 5 mg/L, inversely, its growth was inhibited at levels higher than 5 mg/L, and it was poisoned at 500 mg/L. Based on the principal component analysis (PCA), the H2O2, O2-, chlorophyll total, chlorophyll a, CAT and proline content explicitly reflected the change in the physiology on the alfalfa and its tolerance under Pb stress.